The role of red mud and cow manure for sustainable post-gold mining land rehabilitation - Suswati, Denah (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
The detrimental ecological impact of unauthorized gold mining in Indonesia is significantly profound, notably apparent in the nutrient-deficient, sandy soils with low pH resulting from the process. These conditions contribute to considerable land productivity decline, especially in West Kalimantan. In response to this challenge, the current study proposes an inventive approach for soil reclamation using red mud residue, derived from bauxite ore extraction, and cow manure as restorative elements. This research delves into a novel soil restoration technique that employs red mud waste (a residual from ore refinement) in conjunction with cow manure as ameliorative agents. A distinct amalgamation of 0.2 kg of red mud and 3 kg of cow manure (T2R3) showcased superior results. The incorporation of this blend resulted in a significant increase in soil pH by 0.93 units, an increase in macronutrient content ranging from 82.84%-503.07%, and plant growth (plant height and stem diameter) increased between 32.85%-54.31% in the treatment with 0.2 kg of red mud and 3 kg of cow manure (T2R3) compared to the lower treatment of 0.1 kg of red mud and 1 kg of cow manure (T1R1). These changes were evident, indicating improved soil fertility and the potential for increased crop yield